Who Said What: A Multi-Country Content Analysis of European Health Organisations’ COVID-19 Social Media Communication - Kompani, Kamyar; Deml, Michael J.; Mahdavian, Farnaz; Koval, Olena; Arora, Sanjana; Broqvist, Hilda (International Journal of Public Health, 2022)
Objectives: As a risk communication tool, social media was mobilised at an unprecedented level during the COVID-19 pandemic. This study examined health authorities’ risk communication on social media in response to the pandemic in 2020. Methods: We quantitively analysed 1,633 COVID-19-related posts from 15 social media accounts managed by official health authorities in Germany, Norway, Sweden, Switzerland, and the United Kingdom. Results: The rate at which the authorities posted about COVID-19 on social media fluctuated throughout 2020. Each account’s posting frequency peaked between March and May 2020, before dropping considerably during the summer. The messages that the organisations focused on also varied throughout the year but covered most risk communication guidelines. Yet, our analysis highlighted themes that were communicated infrequently, such as long COVID or exercising during the pandemic. Conclusion: With more individuals now following health authorities on social media, platforms such as Instagram hold great potential for future risk communication campaigns and strategies.